Hilo. Book 9, Gina and the last city on Earth - Winick, Judd (Winick, Judd. Hilo, 2023)
"There's only one person brave enough to save Earth once and for all, and that's Gina. The cost will be great. But with the help of one magical warrior cat, one flying bearacat, and a whole world that believes in her, Gina's going to try. Get ready for the most shocking Hilo yet--with more twists, more turns, more monsters, and more surprises than ever before. Because sometimes we're the hero the world needs!"--